An empirical analysis of aggregate household portfolios - Normandin, Michel; St-Amour, Pascal (Journal of Banking & Finance, 2008)
This paper analyzes the important time variation in US aggregate household portfolios. To do so, we first use flexible descriptions of preferences and investment opportunities to derive household optimal decision rules that nest static, myopic, and non-myopic portfolio allocations. We then compare these rules to the data through formal statistical analysis. Our main results reveal that: (i) static and myopic investment behaviors are rejected, (ii) non-myopic portfolio allocations are supported, and (iii) the Fama–French factors best explain empirical portfolio shares.